Time to Frequency Domain Analysis of Narrow Band Antennas - Sajjad Ur Rehman; Majeed A. S. Alkanhal (International Journal of Antennas and Propagation)
This paper presents system modeling of three different single band antennas using the singularity expansion method (SEM). To acquire the accurate physical complex poles and the corresponding residues of the narrow band antenna model, an enhanced Matrix Pencil (MP) method has been applied to the impulse response of the antennas. A delayed time parameter T is introduced to enhance the performance of the MP method to extract the actual physical poles and eliminate the nonphysical poles caused by the early time response of the narrow band antennas. The poles extracted by the enhanced MP method are located precisely within the single operating band of each antenna. The one set of the developed parameters is used to accurately characterize narrow band antennas in both time and frequency domains. The far field impulse response of a fabricated single band microstrip antenna has been measured in the laboratory and then reconstructed precisely using the SEM based model with the proposed MP scheme.